Development and Pilot Test of the RAND Suicide Prevention Program Evaluation Toolkit - Acosta, Joie D. (RAND Corporation, 2013)
The Defense Centers of Excellence for Psychological Health and Traumatic Brain Injury asked RAND to draw from the scientific literature and create a toolkit to guide future evaluations of suicide prevention programs. This report is a companion to the RAND Suicide Prevention Program Evaluation Toolkit and provides additional background on its development and testing.